2014
DOI: 10.1139/apnm-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol supplementation does not augment performance adaptations or fibre-type–specific responses to high-intensity interval training in humans

Abstract: The present study examined the effect of concurrent exercise training and daily resveratrol (RSV) supplementation (150 mg) on training-induced adaptations following low-dose high-intensity interval training (HIIT). Sixteen recreationally active (∼22 years, ∼51 mL·kg(-1)·min(-1)) men were randomly assigned in a double-blind fashion to either the RSV or placebo group with both groups performing 4 weeks of HIIT 3 days per week. Before and after training, participants had a resting muscle biopsy taken, completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 43 publications
1
73
1
Order By: Relevance
“…These adaptations were more robust in type I fibers, as only type I fibers in the RG displayed an increase in SDH activity. These data support previous work in healthy individuals, which has shown that both ET and HIIT increase various markers of mitochondrial content and have a similar response in type I and II fibers (47,49). It was surprising that neither ET nor HIIT increased CS activity in the current study in the RG.…”
Section: Discussionsupporting
confidence: 92%
“…These adaptations were more robust in type I fibers, as only type I fibers in the RG displayed an increase in SDH activity. These data support previous work in healthy individuals, which has shown that both ET and HIIT increase various markers of mitochondrial content and have a similar response in type I and II fibers (47,49). It was surprising that neither ET nor HIIT increased CS activity in the current study in the RG.…”
Section: Discussionsupporting
confidence: 92%
“…This finding ties in well with the study by Olesen et al [32], in which resveratrol blunted the positive effects of exercise training. In contrast, Scribbans et al found that resveratrol in addition to exercise had positive effects on muscle metabolism with an increase in mitochondrial capacity [33], while others found no effect in humans [34]. Most rodent studies have found positive effects of resveratrol on muscle function [5,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is growing support that resveratrol may be a beneficial approach to remodel skeletal muscle in humans. Whilst the data from Timmers et al (2011) was encouraging, recently Scribbans and colleagues (2014) reported that resveratrol supplementation during exercise training in healthy individuals can result in a maladaptive response in exercise-stimulated gene expression [176]. In agreement with this observation, Gliemann et al (2013) showed that resveratrol supplementation in combination with high-intensity training in older men not only blunted the increase in maximal oxygen uptake observed in the placebo group, but also eradicated the effects of the exercise to reduce low-density lipoprotein, total cholesterol and triglyceride concentrations in the blood [177].…”
Section: Nicotinamide Riboside (Nr)mentioning
confidence: 99%